2016
DOI: 10.2147/ott.s116373
|View full text |Cite
|
Sign up to set email alerts
|

Association between proto-oncogene mutations and clinicopathologic characteristics and overall survival in colorectal cancer in East Azerbaijan, Iran

Abstract: BackgroundColorectal cancer (CRC) is the third-most common cancer in Iran. The increasing incidence of CRC in the past three decades has made it a major public health burden in the country. This study aimed to determine any relationship of specific mutations in CRCs with clinicopathologic aspects and outcome of patients.Materials and methodsThis study was conducted on 100 CRC patients by the case-only method. Polymerase chain-reaction products were analyzed by Sanger sequencing, and sequence results were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…All studies are case-control studies published between 2006 and 2016. Six studies were studied from Tehran (Central of Iran) (Bishehsari et al, 2006;Roudbari et al, 2016;Shemirani et al, 2011;Sobhani et al, 2010;Tameshkel et al, 2016;Vakil et al, 2016), one study from Shiraz (Southwest of Iran) (Omidifar et al, 2015), two studies from Kermanshah (Western of Iran) (Amirifard et al, 2016;Payandeh et al, 2016), one study from Tabriz (Northwestern of Iran) (Dolatkhah et al, 2016), and one study from South Khorasan (Eastern of Iran) (Naseri et al, 2016). All studies included 1814 CRC patients that mean age of the patients was 57.5 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies are case-control studies published between 2006 and 2016. Six studies were studied from Tehran (Central of Iran) (Bishehsari et al, 2006;Roudbari et al, 2016;Shemirani et al, 2011;Sobhani et al, 2010;Tameshkel et al, 2016;Vakil et al, 2016), one study from Shiraz (Southwest of Iran) (Omidifar et al, 2015), two studies from Kermanshah (Western of Iran) (Amirifard et al, 2016;Payandeh et al, 2016), one study from Tabriz (Northwestern of Iran) (Dolatkhah et al, 2016), and one study from South Khorasan (Eastern of Iran) (Naseri et al, 2016). All studies included 1814 CRC patients that mean age of the patients was 57.5 years.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included 1814 CRC patients that mean age of the patients was 57.5 years. In more studies, the prevalence of CRC in males was more than females (Amirifard et al, 2016;Bishehsari et al, 2006;Dolatkhah et al, 2016;Naseri et al, 2016;Omidifar et al, 2015;Payandeh et al, 2016;Roudbari et al, 2016;Shemirani et al, 2011;Tameshkel et al, 2016;Vakil et al, 2016). Number of mutations in codon 12 and 13 and also mutant amino acid in codon 12 has been shown in Table 1 that Gly is normal amino acid in codon 12 and can change to other amino acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Wnt signaling pathway is closely associated with BRAF mutation. Several studies have revealed very low incidence (0% -3.7%) of BRAF mutation in Asian CRCs 21,22 . Since we did not find any BRAF mutations in the same CRC samples as our previous study, this may evidence of the absence of any APC truncated mutation pattern 21 .…”
Section: Discussionmentioning
confidence: 99%
“… 4 - 6 Based on the latest article published by the International Agency for Research on Cancer (2018Globocan IARC), in 2018, Colorectal Cancer consists 10.2% of all cancer cases and 9.2% of cases of cancer mortality. 7 Over 1.8 million new colorectal cancer and 881000 deaths were estimated in 2018. The lowest incidence of Colorectal Cancer is in Africa and southern Asia and the highest rate is in male population of the Republic of Korea and in female population of Macedonia.…”
Section: Introductionmentioning
confidence: 99%